2015
DOI: 10.4236/fns.2015.63032
|View full text |Cite
|
Sign up to set email alerts
|

Effects of <i>Biebersteinia multifida</i> DC. Root Extract on Physical Stamina in Male Mice

Abstract: Biebersteinia multifida DC. has been used for the purpose of development of physical strength in iranian folk medicine. In the present study, we investigated the effect of Biebersteinia multifida DC. root extract on performance of the Forced Swimming Test (FST), and on blood biochemical parameters related to fatigue: Blood Urea Nitrogen (BUN), Creatine Kinase (CK), Lactic Dehydrogenase (LDH), Glucose (Glc), and Total Protein (TP). Biebersteinia multifida DC. root extract was orally administered to mice at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Among the four well-known Biebersteinia spp., only B. heterostemon and B. multifida have been commonly applied as traditional herbal medicines to treat musculoskeletal disorders, bone fractures and skin diseases [7,25,55]. In China, B. heterostemon plants are widely distributed in Qinghai-Tibetan Plateau, and have been administered as traditional Tibetan medicines [20,56].…”
Section: Applications In Traditional Medicinesmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the four well-known Biebersteinia spp., only B. heterostemon and B. multifida have been commonly applied as traditional herbal medicines to treat musculoskeletal disorders, bone fractures and skin diseases [7,25,55]. In China, B. heterostemon plants are widely distributed in Qinghai-Tibetan Plateau, and have been administered as traditional Tibetan medicines [20,56].…”
Section: Applications In Traditional Medicinesmentioning
confidence: 99%
“…The anti-fatigue effect of B. multifida root extract was also validated in a forced swimming test (FST), and the biochemical parameters in the blood related to fatigue were measured [7]. The results demonstrated the potential benefit of B. multifida root extract as an anti-fatigue material, and showed that it improved physical stamina [7]. These properties and effects might account for the fact that B. multifida has been used in Iranian folk medicine to enhance physical strength [10].…”
Section: Anti-fatigue and Anxiolytic Effectsmentioning
confidence: 99%
See 1 more Smart Citation